Cardiology in Family Practice A Practical Guide - Hollenberg, Steve; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2006)
The primary care physician (PCP) is the front line of defense against cardiovascular disease, managing a patient's cardiovascular illness and coordinating care with a cardiologist. As such, the PCP needs to have on hand all the most recent information on the diagnosis, treatment, and prevention of common cardiac problems. In Cardiology in Family Practice: A Practical Guide, Steven Hollenberg, MD, and Tracy Walker, MD, undertake to provide primary care physicians with the latest medical and scientific knowledge they need to treat most of the preventive and acute cardiovascular problems they will encounter and to understand clearly when to refer patients to a cardiologist. Writing in an easy-to-read format-background, diagnosis, and disease management-and emphasizing practical techniques of evaluation and treatment, the authors explain the basic mechanisms underlying cardiovascular disease states and the treatment strategies that arise from them. Topics range from acute coronary syndromes, arrhythmias, and hyperlipidemia, to hypertension, pericardial diseases, valvular disease, and stable angina. Simple but clinically useful references point the inquiring physician to the most useful sources of additional information. Concise and up to date, Cardiology in Family Practice: A Practical Guide offers a clear understanding of today's standard approaches to cardiovascular illnesses and a highly valuable resource when specific questions arise during the care of patients.
Acute Coronary Syndromes -- Arrhythmias -- Prevention of Bacterial Endocarditis -- Congestive Heart Failure -- Hyperlipidemia -- Hypertension -- Pericardial Diseases -- Stable Angina -- Valvular Diseases.
Keywords: General practice (Medicine).; General Practice / Family Medicine